System spectral analysis of the fractal ultra-wideband signals - Chernogor, L.F.; Kravchenko, S.G.; Lazorenko, O.V. (Вопросы атомной науки и техники, 2015)
The theoretical basis and practical peculiarities of the system spectral analysis are briefly considered. The necessity and the expediency of simultaneously application of different linear and non-linear integral transforms during the system spectral analysis performance are explained. The system spectral analysis usage for investigations of the time-frequency structure of the fractal ultra-wideband signals is shown to be effective and useful. Стисло розглянуто теоретичні засади та практичні особливості системного спектрального аналізу. Роз’яснено необхідність і доцільність одночасного використання різних лінійних і нелінійних інтегральних перетворень для проведення системного спектрального аналізу. Продемонстровано, що застосування системного спектрального аналізу для дослідження часо-частотної структури фрактальних надширокосмугових сигналів є корисним та ефективним. Кратко рассмотрены теоретические основы и практические особенности системного спектрального анализа. Разъяснена необходимость и целесообразность одновременного применения различных линейных и нелинейных интегральных преобразований для проведения системного спектрального анализа. Показано, что использование системного спектрального анализа для исследования время-частотной структуры фрактальных сверхширокополосных сигналов является полезным и эффективным.